2017
DOI: 10.1159/000471761
|View full text |Cite
|
Sign up to set email alerts
|

Pre-ESRD Dementia and Post-ESRD Mortality in a Large Cohort of Incident Dialysis Patients

Abstract: Background: Conservative management may be a desirable option for elderly, fragile, or demented patients who reach end-stage renal disease (ESRD), yet some patients with dementia are placed on renal replacement therapy nonetheless. Methods: From a nationwide cohort of 45,076 US veterans who transitioned to ESRD over 4 contemporary years (October 1, 2007 to September 30, 2011), we identified 1,336 (3.0%) patients with International Classification of Diseases, Ninth Revision, Clinical Modification code-based dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…hospitalization. These findings are consistent with those of recent studies, which reported that the presence of dementia before dialysis increased the risk of postdialysis mortality by 19% to 30% [18,19]. Multiple factors, such as increased cardiac and cerebrovascular risks [19], frailty [14,20], impeding treatment adherence [21], and comorbidities [22], may contribute to post-ESKD mortality in dementia.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…hospitalization. These findings are consistent with those of recent studies, which reported that the presence of dementia before dialysis increased the risk of postdialysis mortality by 19% to 30% [18,19]. Multiple factors, such as increased cardiac and cerebrovascular risks [19], frailty [14,20], impeding treatment adherence [21], and comorbidities [22], may contribute to post-ESKD mortality in dementia.…”
supporting
confidence: 92%
“…In addition, the Korean population has been rapidly growing older, and the age-standardized annual prevalence rate of AD in Korea has increased from 3.17 in 2006 to 15.75 in 2015 (events per 1,000 persons) [26]. A cohort study of veterans in the United States conducted between 2007 and 2011 revealed that 3.0% of incident dialysis patients had dementia, highlighting that nearly 50% of patients with dementia died within a year of dialysis initiation [18]. Given the increased prevalence and aggravated mortality risk associated with dementia in patients with ESKD, cognitive assessment of patients with ESKD before dialysis initiation may be instructive.…”
mentioning
confidence: 99%
“…A substantial proportion of this population cohort (29%) had chronic kidney disease. Dementia is associated with an increased risk of death in individuals with end stage renal disease 39 and in dialysis patients 37 . Hospitalization is often required for older adults with glomerular diseases due to comorbidity and higher risk of cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…We studied longitudinal data from the Transition of Care in CKD (TC-CKD) study, a historical cohort study examining US veterans with incident ESRD transitioning to dialysis from October 1, 2007 through March 31, 2014. 27,28 A total of 85,505 US veterans were identified from the US Renal Data System (USRDS) 29 as a source population. The algorithm for the cohort definition is shown in Figure 1.…”
Section: Study Populationmentioning
confidence: 99%